The application of simulated moving bed chromatography for the separation between 2,6-and 2,7-dimethylnaphthalene - Kim, YD; Lee, JK; Cho, YS (KOREAN INST CHEM ENGINEERS, 2001)
The possibility of applying SMB chromatography for the separation of 2,6-DMN and 2,7-DMN was investigated by numerical simulation based on the single column chromatography experimental data. It was found that 2,6-DMN could be separated from 2,7-DMN in the ODS-modified silica gel by using methanol and water as the mobile phase. A systematic method of obtaining model parameters for the SMB simulation from single column chromatography experiments was presented. The adsorption isotherms of 2,6-DMN and 2,7-DMN were obtained by the pulse method. The mass transfer kinetics was very fast, indicating that the mobile phase and the stationary phase are very close to equilibrium for both 2,6-DMN and 2,7-DMN. SMB simulation was performed by using the model parameters. Pure 2,6-DMN and 2,7-DMN can be obtained by selecting suitable operating conditions, indicating that SMB chromatography can be employed to separate 2,6-DMN and 2,7-DMN. The influence of operating parameters (feed flow rates, raffinate flow rate, and switch time) was also investigated to recommend the optimum operating conditions.
Keywords: ADSORPTION; OPTIMIZATION